2008
DOI: 10.1111/j.1365-2109.2008.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotic bacteria in the rearing of Senegalese sole (Solea senegalensis) larvae

Abstract: Three candidate probiotics, which had shown antimicrobial activity in vitro against two ¢sh pathogens, were used in the rearing of Senegalese sole larvae and postlarvae. These probiotics improved the survival of starved sole yolk-sac larvae. A feeding experiment of sole larvae and postlarvae comprised three treatments: A, B and C. Cultures of aVibrio sp. (2J18) were added to treatment A, whereas a gram-positive (J84) and a Shewanella sp. strain (2J27), were added to treatment B, while in a control treatment C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…Addition of probiotics in live food may have several purposes: (i) inoculation of bacteria that have a positive effect on the growth and survival of the live feed organisms in culture (Ii et al 1997; Rombaut, Dhert, Vandenerghe, Verschuere, Sorgeloos & Verstraete 1999; Douillet 2000; Dhert et al 2001); addition of bacteria that limit the growth of opportunistic bacteria harmful for the Artemia and the larvae (Gatesoupe, Arakawa & Watanabe 1989; Makridis 2000) and (iii) addition of bacteria that may colonize the fish larvae and may have a positive effect on the growth and survival rates of the larvae (Makridis, Martins, Reis & Dinis 2008).…”
Section: Rotifersmentioning
confidence: 99%
“…Addition of probiotics in live food may have several purposes: (i) inoculation of bacteria that have a positive effect on the growth and survival of the live feed organisms in culture (Ii et al 1997; Rombaut, Dhert, Vandenerghe, Verschuere, Sorgeloos & Verstraete 1999; Douillet 2000; Dhert et al 2001); addition of bacteria that limit the growth of opportunistic bacteria harmful for the Artemia and the larvae (Gatesoupe, Arakawa & Watanabe 1989; Makridis 2000) and (iii) addition of bacteria that may colonize the fish larvae and may have a positive effect on the growth and survival rates of the larvae (Makridis, Martins, Reis & Dinis 2008).…”
Section: Rotifersmentioning
confidence: 99%
“…The dosing of probiotics at this stage is critical, as superfluous numbers of bacteria could accumulate in the rearing system and deteriorate the environmental conditions for the larvae. On the contrary, the addition of probiotic bacteria in the feed of postlarvae and juveniles, where the stomach barrier has already been established, has shown that the presence of bacteria in the gut is dependent on the continuous addition of bacteria via the feed, so that the true colonization of intestinal epithelium is under question (Makridis et al. 2008).…”
Section: Steering Larval Microbial Communities To the Benefit Of The mentioning
confidence: 99%
“…Lactobacillus acidophilus has been also shown to promote growth rate in African catfish (Al‐dohail, Hashim & Aliyu‐paiko 2009), and the same positive impact has been reported with other bacteria such as, Vibrio spp. in fingerlings of sea bass Dicentrarcus labrax L. and Senegalese sole Solea senegalensis K. (Makridis, Martins, Reis & Dini 2008; Rengpipat, Rueangruklikhit & Piyatiratitivorakul 2008). Other types of probiotics based on either pure yeast preparations or mixtures of bacteria and yeast (Aly et al 2008; Abdelhamid, Mehrin, El‐barbary, Ibrahim & Abdel‐wahab 2009; He, Zhou, Liu, Shi, Yao, Ringo & Yoon 2009) were also shown to enhance survival and growth rates in tilapia and African catfish.…”
Section: Introductionmentioning
confidence: 99%